Molecular epidemiologic analysis of Vibrio cholerae O1 isolates by pulsed-field gel electrophoresis. - Mahalingam, S.; Cheong, Y.M.; Kan, S.; Yassin, R.M.; Vadivelu, J.; Pang, T. (American Society for Microbiology, 1994)
Isolates of Vibrio cholerae O1 El Tor from two well-defined cholera outbreaks in Malaysia were analyzed by using pulsed-field gel electrophoresis (PFGE). Isolates from sporadic cases occurring during the same time period were also studied. Digestion of chromosomal DNA from these isolates of V. cholerae O1 with restriction endonucleases NotI (5'-GCGGCCGC-3') and SfiI (5'-GGCCNNNN-3'), followed by PFGE, produced restriction endonuclease analysis (REA) patterns consisting of 13 to 24 bands (ranging in size from 46 to 398 kbp). Analysis of the REA patterns generated by PFGE after digestion with NotI and SfiI suggested the clonal nature and close genetic identity of the isolates obtained during each of the two outbreaks (Dice coefficient, 0.93 to 1.0). Although they had very similar REA patterns, the two outbreak clones were not identical. Isolates of V. cholerae O1 from sporadic cases, on the other hand, appeared to be much more heterogeneous (five different REA patterns detected in the five isolates tested; Dice coefficient, 0.31 to 0.81) than those obtained during the two outbreaks. We conclude that PFGE of V. cholerae O1 chromosomal DNA digested with infrequently cutting restriction endonucleases is a useful method for molecular typing of V. cholerae isolates for epidemiological purposes.